Pabrik Bulu Mata Palsu dan Ruang Kuasa Perempuan Buruh (Kajian Etnografis di Desa Pasunggingan, Kecamatan Pengadegan, Kabupaten Purbalingga, Jawa Tengah) - Nurlaili Khikmawati (IAIN Syekh Nurjati Cirebon, 2020)
The study regarding women labor is always interesting to done. This is due to the domestic roles of women that women labor has a double burden for work in the factory and work in the household/domestic area. In addition, the placement of women in the domestic area makes